Care transition strategies in Latin American countries: an integrative review - Maria Alice Dias da Silva Lima; Ana Maria Müller de Magalhães; Nelly Donszelmann Oelke; Giselda Quintana Marques; Elisiane Lorenzini; Luciana Andressa Feil Weber; Iris Fan (Universidade Federal do Rio Grande do Sul, 2018)
Abstract OBJECTIVE To identify and analyze available literature on care transition strategies in Latin American countries. METHODS Integrative literature review that included studies indexed in PubMed, LILACS, Web of Science Core Collection, CINAHL, SCOPUS databases, and the Scientific Electronic Library Online (SciELO), published in Portuguese, Spanish or English, between 2010 and 2017. RESULTS Eleven articles were selected and the strategies were grouped into components of care transition: discharge planning, advanced care planning, patient education and promotion of self-management, medication safety, complete communication of information, and outpatient follow-up. These strategies were carried out by multidisciplinary team members, in which nurses play a leading role in promoting safe care transitions. CONCLUSIONS Care transition activities are generally initiated very close to patient discharge, this differs from recommendations of care transition programs and models, which suggest implementing care transition strategies from the time of admission until discharge.